Specification for a Process Planning Enabling Platform (1995)
The objective of this research is the specification of an enabling platform for process planning system development -- This work was done under a contract issued by Computer Aided Manufacturing-International to the University of Illinois -- An analysis framework is developed that integrates inter-related process planning activities by transforming inputs and controls through mechanisms into outputs -- An object-oriented approach is used to define the object model and thereby facilitate the configuration of a process planning system by providing standardised data objects and fundamental library routines -- The proposed software structure is layered with specific modules designed to support integration and data exchange -- The development domain is machining and includes part understanding, process selection and ordering, equipment specification, setup and operation planning, manufacturability analysis, and plan evaluation and documentation